Twitter marketing for dummies - Lacy, Kyle. (Hoboken, NJ : Wiley Pub., 2011)
Presents an introduction to using Twitter as a marketing tool, describing how to communicate effectively with customers and incorporate a marketing strategy into a mix of new and old media.
Introduction -- The future of Twitter in business -- Building and implementing your Twitter marketing road map -- Devising online strategies for Twitter marketing domination -- Implementing Twitter strategies for offline marketing domination -- The part of tens.
Includes index.
Keywords: Twitter; Twitter (Web site); Internet marketing; Internet marketing; Social networking